Effect of New Kypho-Remainder Orthosis on Curve Intensity in Adults With Postural Hyper Kyphosis - Omid Torkaman; Mojtaba Kamyab; Taher Babayi; Hasan Ghandhari (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective Increase in the normal sagittal curvature (hyper kyphosis) may occur in individuals after skeletal maturity due to the poor postural habits and muscular weaknesses. Failure of changing these postural habits or strengthening the postural muscles may lead to deformities that cause pain and discomfort. The current study aims at determining the effect of a novel mechanical reminder “Kypho-remainder Orthosis” on the intensity of the curvature in individuals with postural hyper-kyphosis. Materials & Methods Fifteen adult participants (9 female, mean age: 26.44 years; 6 male, mean age: 25.66 years) whose X-rays reported over 45 degrees of kyphosis were included in the trial. After the initial evaluations and assessments, each individual was asked to wear the kypho-remainder 8 hours a day for 6 weeks. The kyphosis curvature was measured before and after the trial period by the inclinometer. The quality of life of the participants was evaluated by SF-36 questionnaire. Results The study represented that wearing the orthosis had a significant effect on the angle of hyper-kyphosis curve index (P=0.000) and the quality of life (P=0.028) of the participants. Age, gender, occupation, and BMI variables did not have any impact on the effectiveness of orthosis in decreasing the hyper-kyphosis curvature. Conclusion Considering the importance of maintaining a proper posture to optimize the muscles activity in preventing deformity and orthosis with a bio-feedback mechanism may be the solution. The long-term effect of using a bio-feedback orthosis indicated that kypho-remainder orthosis can significantly improve the kyphosis curve in individuals with postural hyper-kyphosis.